2018
DOI: 10.3390/nano8070529
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Shape Alteration and Size Separation of Surfactant-Free Silver Particles Synthesized by Laser Ablation in Acetone during Long-Period Storage

Abstract: The technique of laser ablation in liquids (LAL) has already demonstrated its flexibility and capability for the synthesis of a large variety of surfactant-free nanomaterials with a high purity. However, high purity can cause trouble for nanomaterial synthesis, because active high-purity particles can spontaneously grow into different nanocrystals, which makes it difficult to accurately tailor the size and shape of the synthesized nanomaterials. Therefore, a series of questions arise with regards to whether pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 58 publications
4
41
0
Order By: Relevance
“…Close observation of particle morphologies also indicated that small particles were also captured by the networks (Fig. 8(c)), similarly to the cases of LAL of Ag 13 and Fe 61 in acetone. The LAL findings lead to the following insights: 1) in presence of liquids, melting during fs laser ablation is significantly inhibited (Fig.…”
Section: Examination Of Ablation Dynamicssupporting
confidence: 60%
See 2 more Smart Citations
“…Close observation of particle morphologies also indicated that small particles were also captured by the networks (Fig. 8(c)), similarly to the cases of LAL of Ag 13 and Fe 61 in acetone. The LAL findings lead to the following insights: 1) in presence of liquids, melting during fs laser ablation is significantly inhibited (Fig.…”
Section: Examination Of Ablation Dynamicssupporting
confidence: 60%
“…Laser ablation offers a versatile platform that can simultaneously induce surface structures [1][2][3] and synthesize nanomaterials [4][5][6][7][8][9][10][11][12][13] for diverse applications, such as wettability control [14][15][16][17] , bioimaging 6,18 , cellular growth manipulation [19][20][21] , lithium-ion batteries 22 , surface enhanced Ra-man scattering (SERS) detection 23,24 , catalysis/ photocatalysis/electrochemical-catalysis 6,7,25 and antifriction [26][27][28][29] . Laser processing also enables the microfabrication of three-dimensional structures and devices 30,31 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the Si−CH 2 signal indicates the decomposition of the 10‐undecenoic acid by pulsed laser irradiation. In fact, several literatures report such an effect by the intense laser irradiation, e. g., the decomposition of water and acetone at the plasma plume and liquid interface . In addition, new peaks appear at ∼1650 cm −1 , and 3400 cm −1 .…”
Section: Resultsmentioning
confidence: 98%
“…In fact, several literatures report such an effect by the intense laser irradiation, e. g., the decomposition of water and acetone at the plasma plume and liquid interface. [34,54,55] In addition, new peaks appear at~1650 cm À 1 , and 3400 cm À 1 . These peaks are corresponding to the stretching vibration modes of C=O and OÀ H. [52,53,56] We can thus conclude that hydrophilic Si-nc is functionalized with carboxylic acid groups originating from 10-undecenoic acid (UA-F: Si-nc).…”
Section: Full Papermentioning
confidence: 96%